Effects of Dexmedetomidine Infusion on Inflammatory Responses and Injury of Lung Tidal Volume Changes during One-Lung Ventilation in Thoracoscopic Surgery: A Randomized Controlled Trial - Chun-Yu Wu; Yi-Fan Lu; Man-Ling Wang; Jin-Shing Chen; Yen-Chun Hsu; Fu-Sui Yang; Ya-Jung Cheng (Mediators of Inflammation)
One-lung ventilation in thoracic surgery provokes profound systemic inflammatory responses and injury related to lung tidal volume changes. We hypothesized that the highly selective a2-adrenergic agonist dexmedetomidine attenuates these injurious responses. Sixty patients were randomly assigned to receive dexmedetomidine or saline during thoracoscopic surgery. There is a trend of less postoperative medical complication including that no patients in the dexmedetomidine group developed postoperative medical complications, whereas four patients in the saline group did (0% versus 13.3%, p=0.1124). Plasma inflammatory and injurious biomarkers between the baseline and after resumption of two-lung ventilation were particularly notable. The plasma high-mobility group box 1 level decreased significantly from 51.7 (58.1) to 33.9 (45.0) ng.ml−1 (p<0.05) in the dexmedetomidine group, which was not observed in the saline group. Plasma monocyte chemoattractant protein 1 [151.8 (115.1) to 235.2 (186.9) pg.ml−1, p<0.05] and neutrophil elastase [350.8 (154.5) to 421.9 (106.1) ng.ml−1, p<0.05] increased significantly only in the saline group. In addition, plasma interleukin-6 was higher in the saline group than in the dexmedetomidine group at postoperative day 1 [118.8 (68.8) versus 78.5 (58.8) pg.ml−1, p=0.0271]. We conclude that dexmedetomidine attenuates one-lung ventilation-associated inflammatory and injurious responses by inhibiting alveolar neutrophil recruitment in thoracoscopic surgery.